BEEHIVE: Sustainable Methodology for Fashion Design - Morais, C. (2014)
The proposal methodology tends to close the “product fashion cycle”, defending the existence of a good waste management policy, so that the clothing are thrown away can be reused or recycled to come back again as material to produce yarn, fabric or knit. Subsequently these materials should be include in the production of sustainable apparel, whose design methodologies should be concerned in providing more durable garments and being possible to transform according to the occasion and the user. With that manner, the Fashion Design Process will be different in all stages of working and according with all stages of the fashion product lifespan. We will present a model with many methodologies to solve different types of problems that will be considered across the Lifecycle in Fashion Clothing.